2016
DOI: 10.1177/0959651816651547
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental study of cavitation performance in sea water hydraulic axial piston pump

Abstract: Cavitation is one of the important elements influencing the performance of sea water hydraulic axial piston pump. To understand the working performance of sea water hydraulic axial piston pump under cavitation effects, a fully dynamic numerical model was developed in this article, which has taken into account the fluid compressibility effect, dynamic processes of gaseous, vaporous, pseudo-cavitation and cavitation damage, and the simulation was conducted through a three-dimensional computational fluid dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…where à indicates the mass transfer among various phases inside the CV, which can be determined by referring SA Imagine and Zhou et al, 23,24 as shown in equation (14).…”
Section: Gas Evolution and Transportationmentioning
confidence: 99%
See 1 more Smart Citation
“…where à indicates the mass transfer among various phases inside the CV, which can be determined by referring SA Imagine and Zhou et al, 23,24 as shown in equation (14).…”
Section: Gas Evolution and Transportationmentioning
confidence: 99%
“…11 Some of the aforementioned models were successfully implemented in commercial computational fluid dynamic solvers. [12][13][14][15] However, these approaches are often highly computationally expensive for simulation in complex fluid domains such as for axial piston machines. The lumped parameter of continuum modeling methods can be used for producing sufficiently accurate results, and a careful study of the overall features of hydraulic machines or components can reduce computational costs.…”
Section: Introductionmentioning
confidence: 99%
“…The internal forces and moments in the axial piston pump are very difficult to be measured. The pressure ripple is often used as the parameter to be compared with simulation results [16,17]. However, the measured pressure ripple is affected by the pump generated flow ripple and the impedance of hydraulic lines, and the simulated and measured results are usually incomparable.…”
Section: Validation Of the Lp Modelmentioning
confidence: 99%
“…Xu et al [8] studied the erosion damage of the valve plate and proposed a computational fluid dynamics (CFD) turbulence model to predict pump dynamic characteristics. Yin et al [9] proposed a complete numerical model, which counted the compressibility effects of fluids and the dynamic processes of gas, steam, pseudo-cavitation and cavitation failure. Lijian S. and Jun Z.…”
Section: Introductionmentioning
confidence: 99%